University Culture: An Analysis at the Level of Research and Educational units (using the Competing Values Framework) - Claudia Rus; Sofia Chirică; Dan Chiribucă; Simona Mălăescu (University Babes-Bolyai, 2017)
The aim of the present study was to investigate the current organizational culture in one large Romanian university, using the Competing Values Framework (CVF). Specifically, we aimed to identify the current overall culture profile and the cultural dominant dimensions at the level of the education and research units. The data was provided by 898 participants, coming from 96 teaching and research units, using a paper-and-pencil form of the ipsative Organizational Culture Assessment Instrument, Part 1. The data was analysed at the level of the organizational units. The results indicated that the overall culture profile of the analysed units comprises a combination of the four cultures, with the predominance of the values of bureaucratic and human relations/clan cultures. This profile was not fully invariant across the six dimensions of the organizational culture: (1). dominant characteristics; (2). organizational leadership; (3). management of employees; (4). organizational glue; (5). strategic emphases, and (6). success criteria. The predominance of the values of bureaucratic and human relations/clan cultures is confirmed in three of the six cultural dimension profiles, namely, the organizational leadership, strategic emphases, and success criteria.